High-Quality Education and Research Collaboration Play a Key Role in the Success of University-Integrated Hubs: Case Study of Kenyatta University - Chandaria Centre for Innovation - Nyiringango, Pascal (African Journal of Education and Practice, 2024)
Purpose: This study was carried out to investigate the role played by High-quality education and research collaboration in the success of university-integrated hubs. Methodology: The study used Kenyatta University -Chandaria Centre for Innovation as the case study. The study employed a qualitative method and was descriptive by design. To cover all the variables, the study employed a theoretical framework that combined; Social Network Theory, Resource-Based View (RBV) Theory, and Institutional Theory. The theoretical framework allowed the researcher to investigate the role of social networks, resources, and institutional arrangements of the university in the success of university-integrated hubs. Findings: The study findings showed that indeed there has been collaboration between researcher and also between the university and the private sector. These social networks together with resources and institutional arrangements at the university have greatly contributed to the success of the ihub. Despite the success however, there are still challenges which include; poor funding for research, high internet costs, lack of national policy on intellectual property, internal weaknesses included; poor state funding, lack of national policy on intellectual property, expensive internet services, non-commercialization of innovations and many others. Unique Contribution to Theory, Practice and Policy: For University embedded ihubs to achieve their intended goal, the study give several suggestions such as increased research funding, fast tracking national policy on intellectual property, access to financial assistance and many others.